The Integration of Islamic Essentialism and Existentialism in the Makhadiyah Educational System at Nurul Cholil Islamic Boarding School - Moh Rieza Salmany; M. Yunus Abu Bakar; Moh Faizin; Mustofa Ali; Usman Yudi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines the integration of Islamic essentialist and existentialist values within the Makhadiyah educational system at Nurul Cholil Islamic Boarding School. The research is motivated by the need for an Islamic educational model that maintains spiritual authenticity while remaining responsive to contemporary social realities. The study aims to analyze how these two philosophical orientations are integrated into pesantren educational practices and how they contribute to santri character formation. This research employed a descriptive qualitative method with a case-study approach. Data were collected through in-depth interviews, participatory observation, and institutional documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data presentation, and conclusion verification. The findings reveal that Islamic essentialism is reflected in the preservation of turats, cultivation of adab, and continuous spiritual habituation that strengthen personal piety. Meanwhile, Islamic existentialism is implemented through community-oriented programs such as guru tugas, nasyrul ‘ilmi, and safari dakwah, which encourage self-actualization and social responsibility. The integration of these dimensions forms a holistic educational paradigm that balances spirituality, intellectuality, and humanity in shaping socially transformative santri. This study contributes theoretically by offering an integrative framework that bridges Islamic essentialism and existentialism within pesantren educational practices. Practically, the findings provide an alternative educational model for Islamic institutions seeking to preserve religious values while fostering students’ social engagement and contextual awareness in contemporary society.